Topological defects and tensionless holography - Bob Knighton; Vit Sriprachyakul; Jakub Vošmera (Journal of High Energy Physics)
Abstract We study topological defect lines in the symmetric-product orbifolds Sym N (X) for a generic seed CFT X. We focus on the defects which preserve the maximum of the S N symmetry. When X is taken to describe the free theory of four fermions and four bosons on a 𝕋4, we construct holographically dual backgrounds describing propagation of tensionless closed strings in the presence of spacetime defects wrapping the conformal boundary. We find a precise match between the spectra of local on-shell closed-string vertex operators in the bulk and the spectra of non-local disorder fields in the spacetime theory.